2020
DOI: 10.1136/bmjopen-2019-035818
|View full text |Cite
|
Sign up to set email alerts
|

Causal beliefs of mental illness and its impact on help-seeking attitudes: a cross-sectional study among university students in Singapore

Abstract: ObjectivesA considerable proportion of those who suffer from mental illnesses in Singapore do not seek any form of professional help. The reluctance to seek professional help could be due to misconceptions about the causes of mental illnesses. Research has shown that help-seeking attitudes can predict actual service use. As young adults are most at risk of developing mental illnesses, this study aims to elucidate the impact of causal beliefs about mental illness on help-seeking attitudes among university stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The same results also reported in the study conducted by Nam et al (2013), which indicated that college students with higher levels of self-stigma have less intention to seek help. According to research conducted by Tan et al (2020), students have low intention to seek help from professionals as they were afraid to be labelled by other people around them. In other words, self-stigma is negatively correlated with help-seeking intention.…”
Section: Discussionmentioning
confidence: 99%
“…The same results also reported in the study conducted by Nam et al (2013), which indicated that college students with higher levels of self-stigma have less intention to seek help. According to research conducted by Tan et al (2020), students have low intention to seek help from professionals as they were afraid to be labelled by other people around them. In other words, self-stigma is negatively correlated with help-seeking intention.…”
Section: Discussionmentioning
confidence: 99%
“…Presentation of the biopsychosocial etiology of depression may have contributed to improved help-seeking attitudes by shifting causal attributions of the illness [ 16 ]. Our earlier analysis showed that the tendency to attribute depression to an individual’s personality was associated with lower psychological openness and higher stigma [ 27 ]. Tan et al reasoned that associating depression with a “weak” character could result in self-blame and shame, thus deterring help-seeking.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, help-seeking propensity was linked to higher psychosocial attribution such as childhood maltreatment or trauma. Tan et al suggested that individuals who endorsed psychosocial attributions were less likely to assume self-blame for the condition and more likely to consider the need to seek help [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another concern that appears persistently in stigma research in Singapore and emerges again in the workplace context in this study is the idea of "loss of face" (Tan et al, 2020a). "Face" represents one's social identity and standing in the social hierarchy in Chinese and other Asian cultures and is thus important to business relations (Dong & Lee, 2007;Tan et al, 2020a).…”
Section: Discussionmentioning
confidence: 96%